2011
DOI: 10.1152/ajpheart.00380.2011
|View full text |Cite
|
Sign up to set email alerts
|

19,20-EpDPE, a bioactive CYP450 metabolite of DHA monoacyglyceride, decreases Ca2+ sensitivity in human pulmonary arteries

Abstract: The aim of this study was to investigate the effect of docosahexaenoic acid monoacylglyceride (MAG-DHA) on human pulmonary arterial tone. Tension measurements on pulmonary arterial tissues demonstrated that MAG-DHA reduced U-46619-induced tone, which is highly sensitive to the H-1152 inhibitor. Results also showed that MAG-DHA treatments decreased RhoA activity levels, which in turn inactivated the Rho-kinase pathway, leading to a reduction in U-46619-induced Ca(2+) sensitivity of permeabilized pulmonary arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 34 publications
0
32
1
Order By: Relevance
“…Indeed, in recent studies, we have demonstrated that n-3 PUFA monoacylglycerides such as MAG-DHA and MAG-EPA display anti-inflammatory effects in animal models of asthma. These effects were likely related to the production of resolvins and protectins (38,39,40,42). Moreover, it has been shown that n-3 DPA and MAG-DPA are likely metabolized by 5-LO, 15-LO, and CYP450 epoxygenase pathways in mediating these effects (12,27,42).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Indeed, in recent studies, we have demonstrated that n-3 PUFA monoacylglycerides such as MAG-DHA and MAG-EPA display anti-inflammatory effects in animal models of asthma. These effects were likely related to the production of resolvins and protectins (38,39,40,42). Moreover, it has been shown that n-3 DPA and MAG-DPA are likely metabolized by 5-LO, 15-LO, and CYP450 epoxygenase pathways in mediating these effects (12,27,42).…”
Section: Discussionmentioning
confidence: 98%
“…Western blots using specific antibodies against the phosphorylated forms of p65 NF-B (p-p65 NF-B) and p38 MAPK (p-p38 MAPK), as well as NF-B, p38 MAPK, IB␣, metalloproteinase (MMP)-2 and MMP-9, vascular endothelial growth factor (VEGF), and ␤-actin proteins, were performed on homogenate fractions or cell lysates, as described previously (38,39,41). Immunostaining of the blots were digitized and analyzed with Lab Image software 2.7.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last 20 yr, the development of in vitro models as well as several studies conducted by various groups, including our laboratory (25), have demonstrated that cytochrome P-450 EPA and DHA metabolites are highly active in smooth muscle cells from both vascular (1) and bronchial beds (28). For instance, the mode of action of 19,20-epoxydocosapentaenoic acid and MAG-DHA has been assessed, and their ability to decrease Ca 2ϩ sensitivity in human pulmonary explants has been demonstrated (23,27). These observations allowed us to put forward the hypothesis that a spectrum of long-chain n-3 PUFA derivatives may be putatively able to reduce local inflammation, wall remodeling, and typical overreactivity in HPAs.…”
mentioning
confidence: 99%
“…MAG-DHA (318 mg/kg) was given orally directly in the back of the mouth with a pipette tip. MAG-DHA treatments were administrated daily (32,35,43). The oral dose of 318 mg/kg corresponds to 60% of the maximum daily dose (5 g/day) allowed for human beings by Health Canada Guidelines.…”
Section: Methodsmentioning
confidence: 99%